Targeted Agents in Ovarian Carcinoma - Murat Oz; Ilker Selcuk; Zafer Arik; Tayfun Gungor (Medicine Science, 2016)
Gynecologic malignancies take an important part in female cancers. Ovarian cancer is the second most common gynecologic cancer with the highest mortality rate in developed countries. Most of the patients need an adjuvant chemotherapy regimen after the initial surgery. Despite their suppressive effect on tumor cells, much toxicity on healthy cells could be seen with these standard chemotherapeutics. In that manner a new way of tumor cell disruption with less toxicity and cancer selective effect is needed, which is called targeted therapy. Moreover this approach could prevent chemo-resistance and increase chemo-sensitivity of the disease. Primary cytoreductive surgery with platinum based chemotherapy shape the initial management of these tumors. However, recently we are on the edge of molecular therapy for this cancer. In this setting we need to identify a dominant biological pathway for tumor progression and discover a functional and structural molecule within this pathway. The new therapeutic modalities with targeted molecules should build up new perspectives insight tumor cell behaviour. Agents against angiogenesis and receptors of growth factors in addition to signalling cascades and intracellular enzymes could shape the individual treatment protocols for cancer survivors. [Med-Science 2016; 5(2.000): 547-61]